MENGELOLA PENOLAKAN TERHADAP PERUBAHAN ORGANISASI Studi pada Frontliner Bank BTN Harmoni Menggunakan Metodologi Serba Sistem Lunak Berbasis Riset Tindakan - Stefanus Sadana; Septo Pramesworo; Rizka Zainab (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2014)
Purpose – This paper, Managing Resistance to Organization Change at Bank BTN Using Soft Systems Methodology based on Action Research (SSM-AR), aims to show how soft systems methodology incorporated in action research (AR) interventions to successfully implement resistance to organization change at Bank Tabungan Negara (BTN). The case study in Bank BTN Harmony branch examined would be useful to branch managers who want to implement policy change in their own organizations. Design/methodology/approach – This project used SSM-AR as its methodology due to flexible, responsive and emergent nature. Findings – SSM-AR is able to address ill-structured problems faced by managers, in collaboration with stakeholders using questioning and reflection. SSM-AR leads to an increased understanding about the problem situation so SSM practitioners can advocate an intellectual framework to guide their research. This research has an additional benefit to overcome obstacles in an academic environment where research processes are still governed based on traditional research methods. Practical implications – The ideas presented in the paper could be particularly useful to a practice-based discipline such as project management where research into its practice is in demand. Originality/value – This paper would be useful to managers that are interested in a demanding methodology to implement organization change in addressing business problems. It demonstrates ways of combining SSM-AR, resulting in a powerful research tool to carry out future rigorous research. Keywords: Soft systems methodology, action research, resistance to change, management research